Saving - What Do We Know, and Why Do We Care? - Servén, Luis; Loayza, Norman; Schmidt-Hebbel, Klaus (World Bank, Washington, DC, 2012)
In principle, there is little reason people, and countries facing different shocks, and income streams should strive for optimal saving rates. But in practice, the inter-temporal choices that underlie saving, are subject to externalities, market failures, and policy distortions, that can cause saving rates to differ from welfare-maximizing levels. The social value of saving could also exceed its private value, because of imperfections in global financial markets. Still, a national saving rate broadly in line with an economy's investment rate, reduces vulnerability to sudden shifts in international capital flows, driven by uncontrollable behavior, or self-fulfilling investor expectations. Yet, as shown by the recent East Asia crisis, high saving alone does not provide complete insurance against the consequences of weak financial systems, or unsustainable exchange rate policies. This is the subject analyzed in this note, through a recent Bank research project, that shows savings has important interactions with income and growth, with resulting implications for policy. Such policies that spur development are an indirect, but effective way to raise private saving. The note further examines this private saving, and public policy, outlining fiscal issues, financial liberalization, and the impact of pension reform. The note reflects on situations where reforms both invite aid, and induce higher investment and growth - so that aid and saving rise together - concluding that aid need not invariably crowd out national saving.